Are nasal steroids effective in children with adenoid hypertrophy? - Solmaz, Fevzi; Aşçıoğlu, Mustafa Erhan; Durgut, Osman; Dikici, Oğuzhan; Haksever, Mehmet; Akduman, Davut (The European Research Journal, 2019)
Objectives: Chronic nasal obstruction is a common disease of childhood. Adenotonsillar hypertrophy plays an important role in obstructive sleep apnea. The topical use of the aerosolized forms of corticosteroids therefore seems the most appropriate route to decrease systemic side effects. The aim of our study is to demonstrate the effect of topical mometasone furoate especially on the adenoid volume in patients without any allergic story.Methods: The study group consisting of 30 males and 25 females was administered topical nasal mometasone furoate steroid treatment. The 20 patients were in the control group where saline solution (0.9% NaCl) treatment was administered consisted of 12 males and 8 females. Nasopharyngeal X-rays before treatment revealed that 25 patients were Grade 2 and 30 patients were Grade 3 according to the Fujioka method. Results: Flexible endoscopy performed before the treatment revealed that 20 patients were Grade 2, 11 patients were Grade 3 and 24 patients were Grade 4. Nasal endoscopies performed after 6 weeks of intranasal topical steroid therapy revealed that 45 patients were Grade 1 and 10 patients were Grade 2. A statistically significant difference was present between endoscopic grades before and after treatment (p < 0.0001). Nasal endoscopies performed after 6 weeks in control group receiving saline solution treatment revealed Grade 2 in 7 patients, Grade 3 in 10 patients and Grade 4 in 3 patients. There was no statistically significant difference between in the prior and later grades of the control group (p = 0.3125). Conclusions: We believe that the use of intranasal steroids (mometasone furoate) for 6 weeks in patients with pediatric chronic nasal obstruction due to adenoid hypertrophy may be an effective treatment modality in alleviating symptoms and decreasing adenoid volume without causing systemic side effects.